Kajian Yuridis Mengenai Kekuatan dan Kepastian Hukum Sertipikat Hak Tanggungan Terhadap Musnahnya Objek Karena Force Majeure - Ni Made Trisna Dewi (Fakultas Hukum, Universitas Warmadewa, 2022)
Mortgage rights are collateral rights imposed on land rights. Mortgage rights are used to bind guarantees in the form of land using a deed made by the Land Deed Maker OfficerArticle 18 the act of Underwriting Rights does not regulate the abolition of Underwriting Rights how is the legal strength and title of the right to loss of objects due to corruption and second, What is the legal certainty at the time of execution of certificates of liability against the destruction of objects due to force majeure. This legal research uses a type of normative legal research that is reviewing and analyzing materials and legal issues. Moving on from the void of norms in the act of the Underwriting Rights related to debt guarantees that have been granted Underwriting Rights to creditors considering the land from the debtor has been destroyed due to natural disaster or force majeure. Method of approach to the Law Approach and Conceptual Approach The legal strength regarding the certificate of mortgage rights to Article 1245 of the Civil Code in the event that the object is destroyed due to natural disasters does not have normative force but does not result in the loss of the debtor's obligation to repay the obligation to the creditor, based on the principle pacta sun servanda. The policy that provides certainty for creditors as a privileged position in the case of accounts payable is by repressive action to enter into a credit insurance agreement that has the value of additional guarantees and preventive actions by making grosse deeds under the force of executive law.